Note on Three Tapestry Hangings inventoried among the Belongings of Mary of Guise, Queen Regent, and of her Daughter, Mary Queen of Scots - Scott-Moncrieff, Robert (Proceedings of the Society of Antiquaries of Scotland, 1917)
The history of the hangings can be divided into three periods. The first extends from September 1561, when the pieces are inventoried as having belonged to the Queen Regent, Mary of Guise, to 1578, when they are inventoried as having been taken over from the Regent Morton by James VI. The second period extends from the reign of James VI. to 1692, at which date they are believed to have been acquired by Mrs Rachel Sinclair or Hog on behalf of her ward William Hogg. The third and last period covers the time from 1692 to the present day. The scenes depicted deal with the history of the rival monarchs Behoboam and Jeroboam, as related in the bible. It is highly unlikely that there should have been two sets of fine needlework dealing with an unusual subject like that of Rehoboam, and consisting of something like the same number of pieces, that one is driven to the conclusion that they are the hangings mentioned in the inventories.